ANALYSIS OF THE CONCEPT OF “SOCIAL COMPETENCE OF PERSONALITY» IN UKRAINIAN AND FOREIGN SCIENTIFIC PAPERS - Yana S. Lukatska (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
New Ukrainian and world realities set new tasks for the higher educational establishments, which are related to the search for new, modern methods that allow to increase the effectiveness of training. Currently, topical are the issues of not only professional but also the personal development of the student forming the priority in the implementation of educational activities in universities, preparation for future professional activities, as well as for successful interaction in society. The concept of «individual social competence» is an important factor in creating a system of educational process which takes into account aspects of professional development, and at the same time the peculiarities of the formation of the student personality. The author analyses the concept of «competence», considers the key competences for lifelong learning, identified by the European Parliament and the Council of the European Union, including social competence, studies the scientific achievements of Ukrainian and foreign scientists, including G. Gedviliene, H. S. Han, K. M. Kemple, U.P. Kanning, M. Horenburg, G.W. Ladd, H. K. Ma, K. Monahan, M. Monnier, O.V. Varetska, N.I. Hlebova, D.V. Hubareva, O.I. Hura, M.O. Doktorovych, I.B. Zarubinska, O.O. Subina, V.M. Shakhrai. They explored different aspects of social competence of different age categories. The author concludes that, despite different interpretations, all scientists agree that social competence is an acquired skill, it can be formed and developed throughout life. It was also determined that the developed social competence determines the status of the individual in society, it affects the success in professional activities. The high level of social competence allows a person not only to be realized in professional activities, but also to influence the processes in society, which in turn determines its stability. The author’s definition of the concept of «individual social competence» is given in the paper; the author concludes that social competence is an integrated ability that contains other competencies: spiritual, civic, communicative, linguistic; the concept of social competence is closely related to professional competence, without the successful interaction of the individual with society it is impossible to acquire the skills and abilities inherent in a qualified specialist. Thus, an important task for modern higher education is the formation and development of social competence of students, which is the key to successful implementation of the future specialist in professional activities. The educational process should be aimed at forming a system of knowledge about interaction in society, understanding the system of social values, ability to cooperate in society, the ability to communicate constructively, because only a socially competent person can.